Hemodialysis Parameters and Pulse Wave Velocity - Miseljic, Sanja; Aziri, Buena; Begic, Edin; Rebic, Damir; Džubur, Alen; Miseljic, Nenad; Mekic, Mevludin; Resic, Halima; Begic, Nedim; Zukic, Fuad (International journal of applied and basic medical research, 2022)
Abstract Aim: The study aimed to evaluate the acute effect of ultrafiltration on the mechanical properties of the aorta using brachial-ankle pulse wave velocity (PWV) before and after hemodialysis (HD). Patients and Methods: This study included 80 patients who were on a long-term HD program. The input variables were anamnestic data, body composition monitor (BCM) parameters, and echocardiography findings. The assessment of hydration status was determined by BCM, whose work is based on the principle of multifrequency bioimpedance spectroscopy. Another diagnostic procedure was the use of an arteriograph apparatus to assess PWV and Augmentation Index (AIx). All measurements were performed before and after dialysis on the middle dialysis day of the week. Results: The participants were divided into two groups based on hydration status: the experimental group consisted of 40 overhydrated participants and the control group consisted of 40 normovolemic participants. Statistically, the following BCM parameters correlated significantly positively with PWV: total body fat (r = 0.222; P < 0.05), overhydration (r = 0.290; P < 0.001), and relative overhydration (r = 0.290; P < 0.001). From echocardiography findings, only left atrial diameter correlated statistically significantly positively with PWV (r = 0.359; P < 0.001). Comparison of the mean PWV values within the experimental group before and after HD showed a statistically significant decrease from 14.32 ± 2.34 m/s to 8.72 ± 1.52 m/s (Z = 3.254; P = 0.0001). Mean PWV values within the control group did not decrease significantly from 13.39 ± 1.32 m/s to 10.39 ± 1.18 m/s (Z = 0.524; P = 0.742). If we compare the mean values of PWV between groups, then before HD treatment, there was no statistically significant difference between groups with PWV values in the experimental group of 14.32 ± 2.34 m/s and the control group of 13.39 ± 1.32 m/s (Z = 0.762; P = 0.852). According to the results of univariate regression analysis before and after HD treatment, only overhydration showed an absolute effect on PWV before and after HD. Conclusion: Overhydration showed an effect on brachial-ankle PWV before and after HD, and brachial-ankle PWV should be followed in HD patients.